2022
DOI: 10.1140/epjs/s11734-022-00649-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: respiratory disease diagnosis with regularized deep convolutional neural network using human respiratory sounds

Abstract: Human respiratory sound auscultation (HRSA) parameters have been the real choice for detecting human respiratory diseases in the last few years. It is a challenging task to extract the respiratory sound features from the breath, voice, and cough sounds. The existing methods failed to extract the sound features to diagnose respiratory diseases. We proposed and evaluated a new regularized deep convolutional neural network (RDCNN) architecture to accept COVID-19 sound data and essential sound features. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…While it is important to note that vocal analysis is not a primary method for COVID-19 diagnosis, it has been investigated as a supplementary or early detection tool. Some studies have found that changes in vocal patterns can be associated with respiratory illnesses, including COVID-19 [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…While it is important to note that vocal analysis is not a primary method for COVID-19 diagnosis, it has been investigated as a supplementary or early detection tool. Some studies have found that changes in vocal patterns can be associated with respiratory illnesses, including COVID-19 [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Future test development should concentrate on overcoming restrictions and enhancing the COVID-19 diagnostic techniques' accuracy, speed, and usability. Kranthi Kumar et al [29] In this paper, Deep CNN (with Max-Pooling) and Deep CNN (without Max-Pooling) are proposed models. KDD-data, ComParE2021-CCS-CSS Data, and NeurlPs2021-data are the datasets utilized in this.…”
mentioning
confidence: 99%